Preparation of Mg-doped coffee waste for efficient removal of methylene blue and lead from water - Pengfei Li; Liang Zhao; Long Li; Kehan Xu; Jibran Iqbal; Zhenbang Tian; Xing Xing; Hui Li; Yaping Hou; Jie Wang; Manman Xu (Heliyon)
Water pollution, particularly from industrial sources, poses severe environmental and health risks, necessitating cost-effective and sustainable solutions. This study investigates the preparation and application of magnesium-doped coffee waste biochar (Mg-CW) for the removal of methylene blue (MB) and lead ions (Pb2+) from water. Mg-CW, synthesized via one-step pyrolysis at 300 °C, demonstrated remarkable adsorption capacities of 1024.88 mg/g for MB and 349.59 mg/g for Pb2+. Adsorption efficiencies were optimal at pH 12 for MB and pH 5 for Pb2+, attributed to enhanced electrostatic interactions and complexation mechanisms. Regeneration studies revealed that Mg-CW retains over 95 % adsorption efficiency after multiple cycles, highlighting its durability and cost-effectiveness. This study provides a scalable and eco-friendly approach for industrial wastewater treatment, utilizing waste-derived materials to address pressing environmental challenges.